Future of Catholic Monasteries on New Monastic Continents: The Case of Africa - Jonveaux, Isabelle (Religions, 2019)
Catholic monasticism in Europe is often associated with a crisis of vocations, of credibility and sometimes the question of closing down. Looking at monasteries outside Europe, especially in Asia and Africa, we observe a dynamic of new foundations and young entrants into the communities. What are the challenges for monasteries in Africa in future decades? To what extent does monasticism experience a gravitational shift from Europe to other continents in the next thirty years? This article seeks to explore the challenges of African monastic communities now and in the future. The first part gives some demographic data which shows the dynamism of African monastic communities. The second part deals with the adaption of monastic life in the local environment; for instance, concerning the liturgy but also the role of the development of monastic communities. In the last part, I discuss the challenges of African monasticism, which is becoming autonomous from its European founders and developing more and more indigenous foundations. This article is based on field inquiries conducted in monastic communities in five countries in Africa between 2013 and 2019.